"... Those could just as well be the rocky mountains..." Consumption, spectacularity and much more in obstetrical ultrasound in Rio de Janeiro at the turn of the century - DOI: 10.3395/reciis.v3i4.217en - Lilian Krakowski Chazan; Ivan da Costa Marques (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2009)
This work calls upon the so called ANT (actor-network theory) to approach the obstetric ultrasound technology as an 'indispensable' technology in prenatal monitoring in Rio de Janeiro at the turn of the 21st century. It does not envisage to build an exhaustive list but rather to perform a set of heterogeneous elements which by acting in juxtaposition configure the specificity of the studied technology, allowing for its delimitation and naming. The hybrid elements that are presented here - equipment, didacticism, assurance, oracle, affections, prestige, market, media, pathology, purification - are configured and understood as agents or actants which simultaneously are: 1) natural but without previously established forms that are already out there to be 'simply' discovered (not "things-in-themselves"); 2) collective but not social if this adjective refers to belonging to an exclusive world of relations of "humans-among-themselves"; and yet 3) narrated but not constituted solely by discourse.The purpose of this work is to perform a distance from the tradition of the great a priori dividers which predominate in the studies of the so-called modern knowledge in the last few centuries: natural x social, public x private, heart x mind, science x belief, human x non-human, male x female, macro x micro, local x global. Our special interest is that, to the extent that this distance is obtained, other landscapes can be reached by Brazilian and Latin American STS (science-technology-society studies) - there, to say it somewhat crudely, that which exists is that which acts, and only hybrids have the capacity to act. The next step of this work, here indicated but not completed, is to study where the actions that configure the above elements take place and by which means (material vehicles) they communicate, articulate and act one upon other among themselves.